Naringenin, a citrus flavanone, enhances browning and brown adipogenesis: Role of peroxisome proliferator-activated receptor gamma - Bae, Jiyoung; Yang, Yang; Xu, Xinyun; Flaherty, Jamie; Overby, Haley; Hildreth, Kelsey; Chen, Jiangang; Wang, Shu; Zhao, Ling (Frontiers in Nutrition, 2022)
Promoting thermogenesis through increasing the activities of functional brown adipose tissues (BAT) has promised new hope for obesity treatment and prevention. Naringenin (NAR) is a flavanone mainly found in citrus fruits. NAR has been reported to decrease body weight, increase energy expenditure in treated mice, and promote browning in human adipocytes. Here, we investigated the effects of NAR on 3T3-L1 adipocytes' browning and β-adrenergic agonist isoproterenol (ISO)-stimulated thermogenic activation and classical murine brown adipogenesis. In addition, we demonstrated the signaling pathways and involvement of peroxisome proliferator-activated receptor gamma (PPARg) in the process. We found that NAR did not increase Ucp1 mRNA expression at the basal (i.e., non-ISO stimulated) condition. Instead, it significantly increased ISO-stimulated up-regulation of Ucp1 and Pgc-1α expression and enhanced thermogenesis in 3T3-L1 adipocytes. NAR enhanced PKA activation and phosphorylation of p38 MAPK downstream of ISO stimulation and activated PPARg. Inhibition of either PKA or p38 by the pharmacological inhibitors or PPARg knockdown attenuated Ucp1 up-regulation by NAR. Moreover, NAR promoted brown adipogenesis as evidenced by increased lipid accumulation, brown marker gene expression, and thermogenesis in murine brown adipocytes, which was also attenuated by PPARg knockdown. Together, our results demonstrate that NAR promotes the development of functional BAT in part through PPARg activation.